Phonological representation: beyond abstract versus episodic - Pierrehumbert, J (Annual Reviews, 2016)
Phonological representations capture information about individual word forms and about the general characteristics of word forms in a language. To support the processing of novel word forms as well as familiar word forms in novel contexts, an abstract level of representation is needed in which many phonetic details and contextual features are disregarded. At the same time, evidence has accumulated that such details are retained in memory and used in processing individual words and indexical features of language. Taken together, these results mean that a hybrid model of phonological representation is needed. The abstract level supports generalizations based on lexical type statistics and fast adaptation to communicative requirements through the reuse of existing categories. A richly detailed level of representation is implicated in word-specific phonetic patterns, the detailed dynamics of regular sound changes, and active associations of phonetic patterns with gender, age, and dialect.